KAJIAN PEMANFAATAN AIR PASANG DAN AMELIORASI TERHADAP PELARUTAN SENYAWA TOKSIK DAN HASIL PADI SAWAH DI TANAH GAMBUT - Agus Supriyo (Universitas Muhammadiyah Purwokerto, 2015)
The goal of this research was study on the usage of tidal water swamps and amelioration on silute of toxsic substance, growth and yield of rice on peat soils. Field experimental was conducted in Pangkoh X Bloch A (Kanamid Jaya village), Kapus District, Central Kalimantan in 2015 DS on peats soil, sapric degree maturity with 60 cm thickness. Factorial experiments were arraged in Spli-split plots designs with foor replications. As a mains plot (usage of tidal water) i,e application of neap tide conserve in sawah plots, flushing water one day befor neap tide next periods (L1) and application of tidal water in neap tide period conseve water one days (24 hours) on sawah plots and flushing water naturaly (Lo). Sub plots (A) two ameliorant and fertilizers level) i.e 4,85 t dolomit + 5,96 t farm yard manure + 119 kg Urea + 119 kg SP 36 + 80 kg KCl/ha (A1) and 50 kg urea + 50 kg SP 36 per ha as a control (Ao). Sub-sub plots (varieties) consisted Martapura and IR 66. Minimum tillage was conducted in plot size 5 m x 6 m, ameliorant was applied in the soil 2 weeks before planting. Seedling were transplanted by 25 days after sowing at 25 cm x 25 cm plant spacing. An experimental were conducted in two seasons i,e wet seasons (WS) and dry seasons (DS). Second experimental were conducted to add urea fertilizer only such as farmer practices. Parameters were colected i.e (a) peat chemichal properties such as Soil-pH, Ecm Avl-P, Exch-H, Exch-Al and Excaheble base such as Ca, Mg, K and Na, (b) Toxsic substant dilute such as H+, Al+3 dan Fe+2-dillute at 2, 4, 6 and 8 weeks after planting (WAP). (c) Yield component and yield rice (conversion of kernel weight at plot size 2,5 m x 2,5 m in a hectares on 14 % water contents. Research result showed that (a) interaction of usage of tidal water at neap tide was conserve in sawah plots during 24 hours and flushing water naturaly (L1) with ameliorant and fertilizer levels (A1) equivalent (4.800 dolomite + 5.860 FYM +119 urea + 119 SP36+79,5 KCl) kg.ha-1 on sparic peats to increase water-pH-air disolved, and to decrease of dilute acidity (disolved-H and disolved-Al) and disolved-Fe.(b) The usage water tide was conserve in sawah plots until one day before next neap tide periods.(Lo) gave rice yield of IR 66 about 3,600 t.ha-1 or to increase 19,50% higher rice yield of Martapura were supported by high of yield component and plant dry weight (c) Application of ameliorant and fertilizer levels (A1) in IR variety gave rice yield 4,360 t.ha-1 on WS and 2,670 t.ha-1 on DS more higher compared to rice yield of CV. Martapura.